Effective correction of genitourinary menopausal syndrome by the method of fractional laser ablation - Yu.E. Dobrokhotova; Ilina I.Yu; Venediktova M.G; Utina M.S; Morozova K.V; Suvorova V.A; Vasilyeva A.S (LCC «Medicine-Inform», 2018)
Effective correction of genitourinary menopausal syndrome by the method of fractional laser ablation Dobrokhotova Yu.E., Ilyina I.Yu., Venediktova M.G., Utina M.S., Morozova K.V., Suvorova V.A., Vasilyeva A.S. Pirogov Russian National Research Medical University, Moscow Aim: to determine the effectiveness and benefits of the FemTouch procedure with AcuPulse (Lumenis) CO2 laser for the treatment of prolapse of pelvic organs of I-II degree, stress and mixed urinary incontinence, vulvovaginal atrophy. Patients and Methods: the study enrolled the patients (n = 53) with prolapse of pelvic organs of I-II degree, mixed urinary incontinence, stress incontinence, vulvovaginal atrophy, dyspareunia. All patients were treated by four sessions of FemTouch procedure with AcuPulse (Lumenis) CO2 laser at intervals of 21-28 days. The results were assessed with the use of PFDI-20 questionnaires (Pelvic Floor Disorders Distress Inventory), FSFI (Female Sexual Function Index), VSQ (The Vulvovaginal Symptom Questionnaire), the vaginal health index (VHI), measurement of pelvic floor muscle strength, sonoelastography, assessment of blood flow in the vaginal walls before and after the treatment. Results: according to the PFDI-20 questionnaire, the median score decreased from 51 (35; 84) to 22 (10.25, 45). According to the FSFI questionnaire, there was a significant increase in the sexual function index. In the study group the average score for the VSQ questionnaire at the first visit was 15.2±5.3, at the last - 5.1±3.3 points. The average score of the pelvic floor muscle strength was 7,8±2,64 before the treatment, and 10,4±1,77 (p<;0.05) after the 4-th CO2 laser treatment session. The control ultrasound examination after treatment showed that 47 (88%) of 53 patients had an increase in the number of imaging vessels in the vaginal wall (p <;0.05). According to sonoelastography, the density of the vaginal walls increased (p <;0.05) in 42 (78%) patients after the treatment. Conclusion: the method of the vulvovaginal fractional laser ablation with FemTouch procedure is highly effective and can be recommended as a monotherapy of urogynecological disorders and pelvic floor dysfunction in women of any age. Key words: genitourinary menopausal syndrome, vulvovaginal atrophy, stress urinary incontinence, CO2 laser. For citation: Dobrokhotova Yu.E., Ilyina I.Yu., Venediktova M.G. et al. Effective correction of genitourinary menopausal syndrome by the method of fractional laser ablation // RMJ. 2018. № 5(I). P. 4-9.